Accelerated Rhodamine B removal by enlarged anode electric biological (EAEB) with electro-biological particle electrode (EPE) made from steel converter slag (SCS). (July 2019) - Feng, Yan; Zhang, Zhijie; Zhao, Youheng; Song, Liang; Wang, Xinwei; Yang, Shumin; Long, Yingying; Zhao, Chunhui; Qiu, Liping
Highlights: Electrobiological particle electrode (EPE) was prepared using steel converter slag. EAEB for RhB, COD and NH4 + -N in dyeing wastewater were operated for 122 days. Higher removal rates of RhB, COD and NH4 + -N were attained in EBEB than BAF. Microbial communities and physicochemical properties explained removal performance. EAEB with EPE is an alternative technology to treat dyeing wastewater. Abstract: Electro-biological particle electrode (EPE) made from steel converter slag (SCS) was used as a particle electrode in an enlarged anode electric biological (EAEB) reactor for Rhodamine B (RhB) wastewater treatment, and its purification performance and microbial community were examined. The results revealed that(1) the EAEB reactor showed much higher average removal rates of RhB, COD and NH4 + -N, i.e. 91.68%, 87.63%, and 90.54%, which meant an increase by 59.86%, 20.48%, and 14.22%, respectively, compared with BAF;(2) The optimum current intensity (CI) for simultaneously removing RhB, COD and NH4 + -N in the EAEB reactor was at 1.00 A; and(3) Methylophilus, Aeromonas, Pseudomonas, Pelomonas and Zoogloea accounted for the main bacterial community in EAEB. Therefore, the EAEB reactor with EPE produced from steel converter slag (SCS) was suitable to simultaneously remove RhB, COD and NH4 + -N.